2019
DOI: 10.5005/jp-journals-10005-1702
|View full text |Cite
|
Sign up to set email alerts
|

One-year Clinical Evaluation of Retention Ability and Anticaries Effect of a Glass Ionomer-based and a Resin-based Fissure Sealant on Permanent First Molars: An In Vivo Study

Abstract: Aim:To evaluate and compare the retention ability, anticaries effect and marginal discoloration when sealed with a glass ionomer-based sealant (Fusion i-seal) and a resin-based fissure sealant (Helioseal-F) on permanent first molars. Materials and methods: Caries free, fully erupted permanent first molars of 50 children between 6 years and 8 years were sealed with pit and fissure sealants under rubber dam isolation. Glass ionomer-based sealant was applied on a permanent first molar and the contralateral molar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Results of RCTs retrieved for this study confirmed previous findings regarding the caries-preventive efficacy of pit and fissure sealants but found no differences in favour of type of sealant material, namely resin- or glass ionomer–based. 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 …”
Section: Resultsmentioning
confidence: 99%
“…Results of RCTs retrieved for this study confirmed previous findings regarding the caries-preventive efficacy of pit and fissure sealants but found no differences in favour of type of sealant material, namely resin- or glass ionomer–based. 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 …”
Section: Resultsmentioning
confidence: 99%
“…A wide variety of materials are used as fissure sealants. However, they can be classified into two primary groups—RS and GS [ 11 ]. Although RSs are commonly preferred and used due to their gratifying retention rates, their placement is technically sensitive because of the hydrophobic Bis-GMA.…”
Section: Discussionmentioning
confidence: 99%
“…No marginal discoloration was recorded on teeth sealed with glass-ionomer fissure sealants; however, minor (6%) marginal discoloration was noted for teeth sealed with a resin fissure sealant. At the same time, 2% of the teeth sealed with glass ionomer-based sealant improved caries while none of the teeth with resin-based sealant improved caries in the one-year clinical study [ 11 ]. However, there was no statistically significant difference between RS and GS in terms of retention rate, anticaries effect, and marginal discoloration in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The representative sealant of this type is Teethmate-F (Kuraray), which shows relatively stable, long-term, low-level fluorine release. In a 1-year clinical trial performed by Mathew et al (93), the preservation rate of Helioseal-F (Vivadent) was 88%, and no secondary caries occurred. Another study showed that traditional fluoride sealants release very low concentrations of fluoride, which are insufficient for realizing antibacterial properties (94).…”
Section: Pit-and-fissure Sealantsmentioning
confidence: 98%